Effects of sodium bicarbonate supplementation on muscular strength and endurance: A systematic review and meta-analysis - Grgic, J.; Rodriguez, F.; Garofolini, A.; Saunders, B.; Bishop, J.; Schoenfeld, J.; Pedisic, Z. (Sports Medicine, 2020)
Background: The effects of sodium bicarbonate on muscular strength and muscular endurance are commonly acknowledged as unclear due to the contrasting evidence on the topic. Objective: To conduct a systematic review and meta-analysis of studies exploring the acute effects of sodium bicarbonate supplementation on muscular strength and endurance. Methods: A search for studies was performed using five databases. Meta-analyses of standardized mean differences (SMDs) were performed using a random-effects model to determine the effects of sodium bicarbonate supplementation on muscular strength (assessed by changes in peak force [N], peak torque [N m], or maximum load lifted [kg]) and muscular endurance (assessed by changes in the number of repetitions performed, isokinetic total work, or time to maintain isometric force production). Subgroup meta-analyses were conducted for the muscular endurance of small vs. large muscle groups and muscular strength tested in a rested vs. fatigued state. A random-effects meta-regression analysis was used to explore possible trends in the effects of: (a) timing of sodium bicarbonate ingestion; and (b) acute increase in blood bicarbonate concentration (from baseline to pre-exercise), on muscular endurance and muscular strength. Results: Thirteen studies explored the effects of sodium bicarbonate on muscular endurance and 11 on muscular strength. Sodium bicarbonate supplementation was found to be ergogenic for muscular endurance (SMD = 0.37; 95% confidence interval [CI]: 0.15, 0.59; p = 0.001). The performance-enhancing effects of sodium bicarbonate were significant for both small (SMD = 0.31; 95% CI: 0.04, 0.59; p = 0.025) and large muscle groups (SMD = 0.40; 95% CI: 0.13, 0.66; p = 0.003). Sodium bicarbonate ingestion was not found to enhance muscular strength (SMD = - 0.03; 95% CI: - 0.18, 0.12; p = 0.725). No significant effects were found regardless of whether the testing was carried out in a rested (SMD = 0.02; 95% CI: - 0.09, 0.13; p = 0.694) or fatigued (SMD = - 0.16; 95% CI: - 0.59, 0.28; p = 0.483) state. No significant linear trends in the effects of timing of sodium bicarbonate ingestion or acute increase in blood bicarbonate concentrations on muscular endurance or muscular strength were found. Conclusions: Overall, sodium bicarbonate supplementation acutely improves muscular endurance of small and large muscle groups, but no significant ergogenic effect on muscular strength was found.